2019
DOI: 10.1177/2396941519856333
|View full text |Cite
|
Sign up to set email alerts
|

Motor speech impairment predicts expressive language in minimally verbal, but not low verbal, individuals with autism spectrum disorder

Abstract: Background and aims: Developmental motor speech impairment has been suspected, but rarely systematically examined, in low-and minimally verbal individuals with autism spectrum disorder. We aimed to investigate the extent of motor speech impairment in this population and its relation to number of different words produced during a semistructured language sample. Methods: Videos of 54 low-verbal and minimally verbal individuals (ages 4;4-18;10) performing portions of a speech praxis test were coded for signs of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 54 publications
3
49
0
Order By: Relevance
“…This diagnosis is given when children show a delay in the development of precise and stable articulation that nevertheless does not meet the full diagnostic criteria for childhood dysarthria or CAS. Furthermore, recent studies of low or minimally verbal children with ASD also show that around a quarter of children show signs of CAS (Chenausky et al, 2019). It seems then that there is perhaps a subgroup of children with ASD that present with either significant or subtle motor speech difficulties, albeit not necessarily meeting the full criteria for CAS.…”
Section: Speech Motor Control In Children With Autismmentioning
confidence: 99%
“…This diagnosis is given when children show a delay in the development of precise and stable articulation that nevertheless does not meet the full diagnostic criteria for childhood dysarthria or CAS. Furthermore, recent studies of low or minimally verbal children with ASD also show that around a quarter of children show signs of CAS (Chenausky et al, 2019). It seems then that there is perhaps a subgroup of children with ASD that present with either significant or subtle motor speech difficulties, albeit not necessarily meeting the full criteria for CAS.…”
Section: Speech Motor Control In Children With Autismmentioning
confidence: 99%
“…Recently, Chenausky et al [ 33 ] examined 54 low-verbal and minimally verbal ASD individuals (ages: 4.4–18) for motor-speech impermanent. The study observed that very few individuals experienced occasional speech, mute speech, and disordered speech.…”
Section: Discussionmentioning
confidence: 99%
“…These children were seen as having severe injuries in different areas with one and another, and because of that, their expressive language and oral motor skills were passable with their abilities. Besides that, Chenausky et al (2019) investigated the extent of motor speech impairment from 54 low-verbal and minimally verbal ASD children. They found that there was a need to develop spoken language interventions to cater especially the minimally verbal individuals with autism.…”
Section: Literature Reviewmentioning
confidence: 99%